Controllable atomic-ratio of CVD-grown MoS2-MoO2 hybrid catalyst by soft annealing for enhancing hydrogen evolution reaction. (13th January 2020) - Kang, Hari; Youn, Jong-Sang; Oh, Inhwan; Manavalan, Kovendhan; Jeon, Ki-Joon
Abstract: MoS2 has been widely researched as a good catalyst for the hydrogen production, however, the electrochemical applications of MoS2 are still limited because of its low electrical conductivity and electrochemically inert basal plane. In this study, hybrids of MoS2 and MoO2 were used to decrease charge transfer resistance of electrodes. The proportions of MoS2 and MoO2 were controlled by soft annealing without a structural change. The coexistence of MoS2 −MoO2 was confirmed by Raman and X-ray diffraction analysis, and the change of chemical compositions (MoS2 to MoO2 ratio) were demonstrated by X-ray photoelectron spectroscopy. By controlling the chemical compositions of MoS2 and MoO2, the optimal ratio of MoS2 and MoO2 (3: 1) showed the highly electrocatalytic activity (η10 : 198 mV, Tafel: 66.8 mV dec −1 ) and outstanding long-term stability compared to other ratios of MoS2 and MoO2 . Graphical abstract: Image 1 Highlights: MoS2 and MoO2 were synthesized on carbon cloth via the CVD and soft annealing. The atomic ratio for MoS2 and MoO2 hybrid was controlled without structural change. The optimal atomic ratio of hybrid catalyst was found for effective hydrogen evolution.